2020
DOI: 10.21037/atm-20-4915
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MACC1-AS1 attenuates microvascular endothelial cell injury and promotes angiogenesis under hypoxic conditions via modulating miR-6867-5p/TWIST1 in human brain microvascular endothelial cells

Abstract: Background: Hypoxia following ischemic stroke is a common cause of brain insults. Mounting evidence suggests that long non-coding RNAs (lncRNAs) play a vital role in regulating certain physiological and pathological processes including ischemic stroke. For the first time, the present study investigated the effects and mechanism of LncRNA MACC1-AS1 on hypoxia-induced human brain microvascular endothelial cells (HBMECs).Methods: LncRNA MACC1-AS1 levels in HBMECs were detected via reverse transcription quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The researchers found that lncRNA HULC was associated with high risk, severe illness, and poor prognosis in patients with acute ischemic stroke ( 40 ). LncRNA MACC1-AS1 alleviated microvascular endothelial cell injury, promoted angiogenesis by regulating mir-6867-5p/TWIST1, and played a protective role in ischemic stroke ( 41 ). In addition, the researchers found that lncRNA RMRP had a protective effect on ischemic stroke by activating the PI3K/Akt signaling pathway through valproate ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers found that lncRNA HULC was associated with high risk, severe illness, and poor prognosis in patients with acute ischemic stroke ( 40 ). LncRNA MACC1-AS1 alleviated microvascular endothelial cell injury, promoted angiogenesis by regulating mir-6867-5p/TWIST1, and played a protective role in ischemic stroke ( 41 ). In addition, the researchers found that lncRNA RMRP had a protective effect on ischemic stroke by activating the PI3K/Akt signaling pathway through valproate ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, increasing evidence also suggests a complex and close relationship between miRNAs and lncRNAs, based on Salmena's hypothesis that lncRNAs may attract miRNAs as molecular sponges and participate in IS angiogenesis by regulating the expression of downstream genes through miRNAs (Mengqi Zhang and Xinyi Lv 2020; Yan et al 2020). For example, Yan et al (2020) showed that LncRNA MACC1-AS1 acts as a ceRNA for miR-6867-5p to regulate TWIST1 to promote cell proliferation, migration and angiogenesis. found that overexpression of lncRNA DANCR enhanced survival and angiogenesis in OGD-treated BMECs through the miR-33a-5p/XBP1s axis.…”
Section: Discussionmentioning
confidence: 99%
“…Then, streptavidin agarose beads (Invitrogen, Carlsbad, CA, USA) were incubated with the cell lysates, and the RNA complex that bound to the beads was eluted and puri ed using TRIzol reagent (Takara, Shiga, Japan). Gene level in the RNA complex was analyzed by RT-qPCR 26 .…”
Section: Rna Pull-downmentioning
confidence: 99%